Echoes of Queen Victoria: A Foucauldian Interrogation of Colonial Legacies in the Construction of the “Good Student” in Nigeria - Jato, Terfa (NIU Journal of Humanities, 2026)
Queen Victoria of 19 th -century expansionist Britain may not have held sovereignty over an amalgamated Nigeria, yet the institutional echoes of her imperial era remain deeply embedded within the country’s pedagogical system. The missionary and colonial schools that proliferated during her reign introduced a pedagogy of obedience, temporal regulation and physical decorum that survived the transition to state sovereignty. Rather than dismantling this foundation, contemporary educational governance has operationally metricised it. Through an archival-genealogical analysis of qualitative policy documents and secondary institutional indicators – specifically school codes of conduct and the West African Examinations Council (WAEC) affective domain grading scales – this study examines how historical imperial imperatives are translated into modern administrative formats. Drawing on Michel Foucault’s analysis of power, normalising judgement and subjectification alongside decolonial critique, the paper interrogates how these quantitative monitoring mechanisms construct the normative category of the "good student". The analysis suggests that by converting qualitative moral traits like obedience and neatness into calculable data points, modern schools function as panoptic apparatuses. This continuous tracking encourages learners to internalise inherited regimes of truth through active self-surveillance, ultimately constraining the critical independent agency required for sovereign citizenship. This study contributes to decolonial dialogues in the sociology of African education by demonstrating that disrupting colonial legacies requires a fundamental deconstruction of the administrative and statistical machinery that measures and validates student identity. Keywords: Echoes of Queen Victoria; Good Student; Nigerian education; Subjectification; Queen Victoria